Improvement of a mathematics teacher’s methodological competence – modern school requirement - SALTANOVSKA, Nadiia (Journal of Education, Technology and Computer Science, 2016)
A teacher’s methodological competence is a system integrated at the functional level and occupies a significant place in professional activities. The improvement of a maths teacher’s methodological competence is influenced by many factors.